The Role of Customer Ratings and Free Shipping Promos on Buying Interest In Tokopedia Application Services - Ilham Abdullah Sanda; Salim Basalamah (Golden Ratio of Marketing and Applied Psychology of Business, 2021)
This study aims to determine the effect of (1) Customer Rating (2) Free Shipping Promo (3) Customer Rating and Free Shipping Promo together on purchase Intention in Tokopedia Application by Universitas Muslim Indonesia’s Students Faculty of Economics and Business Class of 2019-2020. The method used in this study is a quantitative research method. Respondents are 100 students of the Universitas Muslim Indonesia, Faculty of Economics and Business, Class of 2019-2020, which were obtained using the purposive sampling technique. This study uses primary data by conducting direct research in the field by giving questionnaires. Data analysis methods used are validity test, reliability test, multiple linear regression analysis, classical assumption test, and hypothesis testing. The results of this study indicate that Customer Rating influences purchase intention in Tokopedia Application, Free Shipping Promo influences purchase intention in Tokopedia Application, Customer Rating and Free Shipping Promo simultaneously affect purchase intention in Tokopedia Application.